VP111 Referral Center For Multiple Myeloma Patient Care. (2017) - Saccilotto, Indara; Bittencourt, Rosane; Fischer, Camila; Quevedo, Amanda; Hirakata, Vania; Picon, Paulo
Abstract : INTRODUCTION: Within the Brazilian Health System, Referral Centers (RCs) are care facilities that provide specialized services. The objective of this study was to evaluate the efficacy of care provided to patients with multiple myeloma (MM) at a specialized Referral Centers (Hospital de Clínicas de Porto Alegre Referral Center for Multiple Myeloma, CRMM-HCPA) and to compare quality of life between patients with MM treated at CRMM-HCPA and those treated at non-RC facilities. METHODS: A 6-month cohort study was conducted in patients with MM receiving thalidomide from the State Health Department and treated at CRMM-HCPA, and patients receiving treatment at other non-RC facilities. Thirty-two patients were included in the study, nineteen from CRMM-HCPA and thirteen from other institutions. To analyze the efficacy of care provided at CRMM-HCPA, the main outcome measure was the time from diagnosis to referral for autologous hematopoietic stem cell transplantation.This outcome measure was assessed using questionnaires specifically designed for this study. Quality of life was also assessed, using the Short-Form 36 Item Health Survey (SF-36) questionnaire. RESULTS: Time from MM diagnosis to referral for autologous hematopoietic stem cell transplantation in each group was measured only in patients aged 65 years (n = 25); of these, 15 were recruited from CRMM-HCPA and 10 from other institutions. In this analysis, there was a significant difference (p = .036) in time elapsed between diagnosis and referral for autologous hematopoietic stem cell transplantation, which was significantly shorter for patients treated at CRMM-HCPA (median, 9 months; Interquartile Range, IQR, 8.5–14.5) than for those treated elsewhere (median, 24 months; IQR, 16–24). On quality of life analysis, there was a significant difference in the Social Functioning, which relates to performance of social activities (p = .02). CONCLUSIONS: The Referral Centers model provided seems to be a more efficient treatment strategy as compared with other health care facilities, as it enabled a reduction in time to transplantation. Patients treated at CRMM-HCPA demonstrated greater ease in performing social activities, with less interference from physical or emotional problems.